Improvement of Asri Jewelry Production Capacity During Covid-19 Pandemic - Ida Ayu Nyoman Yuliastuti; Putu Kepramareni; Anak Agung Putu Wiwik Sugiantari; I Ketut Sudipta Giri (AIBPM Publisher, 2020)
This study aims to determine strategies for increasing Asri Jewelry production capacity by continuing to apply health protocols during the Covid-19 pandemic. They are socialization, procurement of hand sanitizers, simple handwashing stations, masks, hand gloves, building materials, assistance in repairs, and expansion as well as arrangement of production sites. The study finds that increased workers' awareness of using masks, and hand gloves, a more comfortable workplace, and more structured flow of production activities. This implies that workers' health and safety are fully guaranteed. The improvements of the production site provide workers the comfortability bringing an increase of the total production capacity of Asri Jewelry.